Mathematical Modeling for the Clarifier Units and Turbidity Parameters in AL-KARAMA Treatment Plant - Abdul-Hameed, Hayder Mohammed (Al-Khwarizmi Engineering Journal, 2017)
The high cost of chemical analysis of water has necessitated various researches into finding alternative method of determining portable water quality. This paper is aimed at modelling the turbidity value as a water quality parameter. Mathematical models for turbidity removal were developed based on the relationships between water turbidity and other water criteria. Results showed that the turbidity of water is the cumulative effect of the individual parameters/factors affecting the system. A model equation for the evaluation and prediction of a clarifier’s performance was developed:Model: T = T0(-1.36729 + 0.037101∙10λpH + 0.048928t + 0.00741387∙alk)The developed model will aid the predictive assessment of water treatment plant performance.The limitations of the models are as a result of insufficient variable considered during the conceptualization.